Amplification of arsenic genotoxicity by TiO2 nanoparticles in mammalian cells: new insights from physicochemical interactions and mitochondria. Issue 8 (14th September 2017) - Wang, Xinan; Liu, Yun; Wang, Juan; Nie, Yaguang; Chen, Shaopeng; Hei, Tom K.; Deng, Zhaoxiang; Wu, Lijun; Zhao, Guoping; Xu, An
Abstract: Titanium dioxide nanoparticles (TiO2 NPs) have shown great adsorption capacity for arsenic (As); however, the potential impact of TiO2 NPs on the behavior and toxic responses of As remains largely unexplored. In the present study, we focused on the physicochemical interaction between TiO2 NPs and As(III) to clarify the underlying mechanisms involved in their synergistic genotoxic effect on mammalian cells. Our data showed that As(III) mainly interacted with TiO2 NPs by competitively occupying the sites of hydroxyl groups on the surface of TiO2 NP aggregates, resulting in more aggregation of TiO2 NPs. Although TiO2 NPs at concentrations used here had no cytotoxic or genotoxic effects on cells, they efficiently increased the genotoxicity of As(III) in human-hamster hybrid (AL ) cells. The synergistic genotoxicity of TiO2 NPs and As(III) was partially inhibited by various endocytosis pathway inhibitors while it was completely blocked by an As(III)-specific chelator. Using a mitochondrial membrane potential fluorescence probe, a reactive oxygen species (ROS) probe together with mitochondrial DNA-depleted ρ 0 AL cells, we discovered that mitochondria were essential for mediating the synergistic DNA-damaging effects of TiO2 NPs and As(III). These data provide novel mechanistic proof that TiO2 NPs enhanced the genotoxicity of As(III) via physicochemical interactions, which were mediated by mitochondria-dependent ROS.